2022
DOI: 10.1159/000521737
|View full text |Cite
|
Sign up to set email alerts
|

A New Potential Antidepressant: Dexmedetomidine Alleviates Neuropathic Pain-Induced Depression by Increasing Neurogenesis in the Hippocampus

Abstract: <b><i>Introduction:</i></b> Studies have suggested dexmedetomidine (DEX) as a potential antidepressant. However, no relevant research exists on its effects and mechanisms in curing depression caused by chronic pain. Therefore, an understanding of DEX’s role in depressive disorders proposes new approaches for antidepressant treatment. <b><i>Methods:</i></b> In this study, C57Bl/6 mice (<i>n</i> = 80) were divided into sham (<i>n</i> = 8) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The subcortical structures primarily consist of the limbic system (i.e., the hypothalamus, the amygdala, the thalamus, and the hippocampus), basal ganglia, and olfactory bulb [ 54 , 55 ], which play roles in chronic pain-induced depression, anxiety, perception, cognition, and memory [ 55 58 ]. Our investigation of the hippocampal formation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The subcortical structures primarily consist of the limbic system (i.e., the hypothalamus, the amygdala, the thalamus, and the hippocampus), basal ganglia, and olfactory bulb [ 54 , 55 ], which play roles in chronic pain-induced depression, anxiety, perception, cognition, and memory [ 55 58 ]. Our investigation of the hippocampal formation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Severe vacuolar degeneration was observed in the DG region. This vacuolar degeneration may be associated with nerve damage resembling depressive symptoms [ 29 , 30 ]. However, the underlying mechanisms of this association require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to DEX’s neuro-regenerative effect, a recent study by Xu et al [ 58 ] conducted among mice found that DEX reduced depression induced by chronic neuropathic pain by promoting cellular proliferation and neuronal differentiation in the dentate gyrus region of the hippocampus. Jimenez-Tellez et al [ 59 ] studied the effects of DEX on cellular homeostasis, viability, growth, and synaptic assembly in rat cortical neurons in vitro , as well as in postnatal day 7 pups to examine whether DEX exposure in vivo could impair learning and memory.…”
Section: Introductionmentioning
confidence: 99%